The Value of OpenNotes for Pediatric Patients, Their Families and Impact on the Patient–Physician Relationship - Sarabu, Chethan; Lee, Tzielan; Hogan, Adam; Pageler, Natalie (Applied Clinical Informatics, 2021)
Background OpenNotes, the sharing of medical notes via a patient portal, has been extensively studied in adults but not in pediatric populations. This has been a contributing factor in the slower adoption of OpenNotes by children's hospitals. The 21st Century Cures Act Final Rule has mandated the sharing of clinical notes electronically to all patients and as health systems prepare to comply, some concerns remain particularly with OpenNotes for pediatric populations.Objectives After a gradual implementation of OpenNotes at an academic pediatric center, we sought to better understand how pediatric patients and families perceived OpenNotes. This article presents the detailed steps of this informatics-led rollout and patient survey results with a focus on pediatric-specific concerns.Methods We adapted a previous OpenNotes survey used for adult populations to a pediatric outpatient setting (with parents of children <12 years old). The survey was sent to patients and families via a notification email sent as a standard practice after a clinic visit, in English or Spanish.Results Approximately 7% of patients/families with access to OpenNotes read the note during the study period, and 159 (20%) of those patients responded to the survey. Of the survey respondents, 141 (89%) of patients and families understood their notes; 126 (80%) found the notes always or usually accurate; 24 (15%) contacted their clinicians after reading a note; and 153 (97%) patients/families felt the same or better about their doctor after reading the note.Conclusion Although limited by relatively low survey response rate, OpenNotes was well-received by parents of pediatric patients without untoward consequences. The main concerns pediatricians raise about OpenNotes proved to not be issues in the pediatric population. Our results demonstrate clear benefits to adoption of OpenNotes. This provides reassurance that the transition to sharing notes with pediatric patients can be successful and value additive.
Keywords: documentation; communication; safety; quality; patient-centered